Analysis and Design of E-Report Card System at SMAN 6 Muaro Jambi Using SSAD - Shela Safitri; Benedika Ferdian Hutabarat; Dewi Lestari (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Manual management of report cards at SMAN 6 Muaro Jambi often leads to recording errors, data loss, and limited access to real-time academic information, which hinders effective communication between schools, teachers, students, and parents. This study aims to analyze and design a web-based E-Report Card system using the Structured System Analysis and Design (SSAD) method as a structured and reliable solution to these challenges. The SSAD approach was applied through several stages, including problem identification, requirement analysis, system design using Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and wireframes, followed by prototype evaluation through usability testing. The evaluation process utilized Maze as a usability testing tool to assess the system’s interface performance using the Mean Adjusted Usability Score (MAUS). The analysis results produced a system design that features structured data flow, an integrated database, and an interactive user interface prototype tailored to stakeholder needs. The usability testing results indicated the highest MAUS score for Students/Parents users (93), while Subject Teachers obtained the lowest score (67), suggesting the need for interface improvement for better task efficiency. Overall, the designed web-based E-Report Card system demonstrates the potential to overcome inefficiencies in manual report card management while enhancing accuracy, transparency, and accessibility of academic information in schools.